REGULATORY ANALYSIS OF THE FCI AS A MECHANISM FOR ACCESS TOHIGHER EDUCATION IN COLOMBIA - López Hernández, Melisa (2022)
Income Contingent Financing (FCI) is one of the systems used in the world to finance admission to higher education. In Colombia it was regulated in 2018, but to date it has not started its operation, as there are legal, budgetary and other difficulties that have not allowed ICETEX to start up. In this article, the Colombian regulation of the FCI is analyzed in a historical key in front of its emergence and comparing it with the way it is used in other countries. The method of synthesis analysis has been adopted, in order to unstructure the object of investigation, to then synthesize its content and thus demonstrate and analyze each part of the structure of the mechanisms for financing higher education in Colombia.